Acute Effects of Wearable Resistance Applied to the Throwing Arm on Performance in Baseball Pitchers - Job, Trey; Cronin, John; Crotin, Ryan; Cross, Matthew (Lippincott, Williams & Wilkins, 2024)
This research examined the acute effects of wearable resistance (WR) placed above and below the elbow of the throwing arm of baseball pitchers on throwing characteristics. Ten high school or collegiate baseball pitchers (19.5 6 2.4 years) performed a randomized throwing assessment with and without WR (100, 150, and 200 g) secured to the throwing arm above and below the elbow. Subjects wore an inertial sensor at the elbow to record arm speed; throwing velocity was measured by radar and temporal aspects (stride phase and pitch phase) measured by video. A repeated measures ANOVA with post hoc analyses was used to test the influence of load magnitude and placement, with statistical significance set at p , 0.05. On average, loading significantly influenced arm speed and throwing velocity (h2 p 5 0.32–0.41, p , 0.05), and the effect of loading varied by placement (i.e., above and below elbow) for the latter (h2 p 5 0.64, p , 0.001). Above elbow loading had no significant effect on the throwing variables measured. For below elbow, there were large decreases in arm speed for 150-g and 200-g loads compared with the unloaded trials (25.13 to 26.52%, d 5 0.82–1.03, p , 0.05) and small-to-moderate decreases in throwing velocity with all loads (21.8 to 22.7%,d50.45–0.67,p,0.01). Overall, WR did not significantly alter phase timing. Our results may indicate the effects of WR differences by placement and may have utility in providing graduated overload to throwing musculature, without clearly influencing timing while throwing.
Keywords: 1106 Human Movement and Sports Sciences; 1116 Medical Physiology; Sport Sciences; 3202 Clinical sciences; 3208 Medical physiology; 4207 Sports science and exercise; arm speed; throwing velocity; loaded throwing; throwing athletes; throwing specific training; pitching